Sensorimotor restriction affects complex movement topography and reachable space in the rat motor cortex - Budri, Mirco; Lodi, Enrico; Franchi, Gianfranco (Frontiers in Systems Neuroscience, 2014)
Long-duration intracortical microstimulation (ICMS) studies with 500 ms of current pulses suggest that the forelimb area of the motor cortex is organized into several spatially distinct functional zones that organize movements into complex sequences. Here we studied how sensorimotor restriction modifies the extent of functional zones, complex movements, and reachable space representation in the rat forelimb MI. Sensorimotor restriction was achieved by means of whole-forelimb casting of 30 days duration. Long-duration ICMS was carried out 12 hours and 14 days after cast removal. Evoked movements were measured using a high-resolution 3D optical system. Long-term cast caused: i) a reduction in the number of sites where complex forelimb movement could be evoked; ii) a shrinkage of functional zones but no change in their center of gravity; iii) a reduction in movement with proximal/distal coactivation ; iv) a reduction in maximal velocity, trajectory and vector length of movement, but no changes in latency or duration; v) a large restriction of reachable space. Fourteen days of forelimb freedom after casting caused: i) a recovery of the number of sites where complex forelimb movement could be evoked; ii) a recovery of functional zone extent and movement with proximal/distal coactivation iii) an increase in movement kinematics, but only partial restoration of control rat values; iii) a slight increase in reachability parameters, but these remained far below baseline values. We pose the hypothesis that specific aspects of complex movement may be stored within parallel motor cortex re-entrant systems.